Systems Engineering for a Circular Economy. Issue 1 (13th September 2016) - Falk, Daniel; Steiber, Bengt‐Göran
Abstract: This paper identifies and describes the principles of circular economy that is getting increased attention in Europe. In 2012 the Ellen MacArthur Foundation, in cooperation with industrial partners, presented a financial report outlining the economic potential inherent in the products of today. With a change in mindset and the use of different business models this potential of $630bn, in Europe alone, can be extracted. This paper discusses the effects of a circular approach and the impact the required shift in business models will have on the fundamental ideas and concepts of today's enterprises. Furthermore the paper states that many of the methods and tools required to perform this change are already accessible today within the systems engineering and logistics engineering domains. The new business models used in a circular economy will require an enhanced integration of these two domains.